Method for producing Fe-Co alloy bar, and Fe-Co alloy bar
By combining the hot rolling and heating straight process, the problem of magnetic characteristics deviation in the long strip Fe-Co alloy rod is solved, and the stable magnetic characteristics of the rod in the length direction is achieved.
Patent Information
- Application Number
- CN202380061964.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-31
- Filing Date
- 2023-07-25
- Publication Date
- 2025-04-08
AI Technical Summary
In long strip Fe-Co alloy rods above 2m, magnetic properties are prone to deviations, and the prior art has not effectively solved this problem.
The hot rolled bar material of 2 m or more was obtained by the hot rolling process, and without solid solution treatment, the heating straight process was performed, and the bar material was heated to 500°C to 900°C, and a tensile stress of a compression ratio of 2.0% to 8.0% was imparted in this process.
The deviation of magnetic properties in the long rod is effectively suppressed, and the magnetic properties stability of the rod in the length direction is ensured.
Smart Images

Figure CN119790179A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for manufacturing a Fe-Co alloy bar and the Fe-Co alloy bar. Background Art
[0002] The rods of Fe-Co alloys represented by Permendur, which is known as an alloy having excellent magnetic properties, are used in various products such as sensors or cylindrical magnetic shields, solenoid valves, magnetic cores, etc. As a method for manufacturing the Fe-Co alloy rods, for example, Patent Document 1 describes the following: after heating the ingot to 1000°C to 1100°C, hot working it into a billet of about φ90 mm, removing scratches on the surface using a lathe, and hot rolling it to about φ6 mm to φ9 mm after heating it to 1000°C to 1100°C, thereby manufacturing the raw material (rod).
[0003] In addition, the applicant of the present application proposed a Fe-Co alloy rod and a method for manufacturing the Fe-Co alloy rod in patent document 2, wherein the Fe-Co alloy rod can stably obtain excellent magnetic properties and has more than 20% of grains with a grain orientation spread (GOS) value of more than 0.5° in terms of area ratio, and the method for manufacturing the Fe-Co alloy rod includes a heating straightening process of heating the hot-rolled material to a temperature of 500°C to 900°C while applying tensile stress.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Laid-Open No. 7-166239
[0007] Patent Document 2: International Publication No. 2021 / 182518 Summary of the invention
[0008] Problems to be solved by the invention
[0009] The Fe-Co alloy rod described in Patent Document 2 has excellent magnetic properties and is a very useful invention. On the other hand, through research by the applicant of the present application, it has been confirmed that in the case of a long bar of more than 2 m, the magnetic properties may deviate in the length direction of the bar. Regarding obtaining stable magnetic properties over the entire length of such a long bar, Patent Documents 1 and 2 do not describe this, leaving room for further research.
[0010] Therefore, an object of the present invention is to provide an Fe—Co alloy rod material capable of suppressing variations in magnetic properties in a long rod material, and a method for producing the same.
[0011] Technical means of solving problems
[0012] The present invention has been made in view of the above-mentioned problems.
[0013] That is, one embodiment of the present invention is a method for manufacturing an Fe-Co alloy rod, comprising: a hot rolling process, in which a Fe-Co alloy billet is hot-rolled to obtain a hot-rolled rod with a length of more than 2 m; and a heating and straightening process, in which the hot-rolled rod is heated to 500° C. to 900° C. while imparting tensile stress in such a way that the compression rate of the rod becomes 2.0% to 8.0%, and no solid solution treatment is performed between the hot rolling process and the heating and straightening process.
[0014] Another embodiment of the present invention is a Fe-Co alloy rod, the average value of the grain orientation spread (GOS) is greater than 0.3° and less than 1.5°, the average grain size number measured in the axial section of the rod is greater than 8.0 and less than 12.0, and the length is greater than 2m.
[0015] Effects of the Invention
[0016] According to the present invention, it is possible to obtain a Fe—Co alloy rod material in which the variation of magnetic properties in the long rod material is suppressed. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] [ Figure 1 ] is a graph showing the compression ratio of the samples of the examples of the present invention.
[0018] [ Figure 2 ] is a graph showing the compression ratio of the samples of the comparative example.
[0019] [ Figure 3 ] is a diagram showing the coercive force distribution of the samples of the examples of the present invention.
[0020] [ Figure 4 ] is a graph showing the coercive force distribution of the samples of the comparative example.
[0021] [ Figure 5 ] is a graph showing the relationship between the compression rate and the coercive force in the samples of the present invention examples and comparative examples. DETAILED DESCRIPTION
[0022] The following is an explanation of the embodiments of the present invention. First, the method for manufacturing the Fe-Co alloy rod of the present invention is explained. The Fe-Co alloy rod of the present invention is a straight rod having a circular (including elliptical) or square cross-sectional shape. The rod of the present embodiment is a round rod having a circular cross-sectional shape unless otherwise specified.
[0023] <Hot-rolled material composition>
[0024] First, in this embodiment, a hot-rolled material of an Fe-Co alloy is prepared. The Fe-Co alloy in the present invention refers to an alloy material containing 95% or more of Fe+Co by mass and 25% to 60% of Co. This can achieve a high magnetic flux density.
[0025] Next, the elements that may be contained in the Fe-Co alloy of the present invention are described. In order to improve the processability or magnetic properties, the Fe-Co alloy of the present invention may contain one or more elements of V, Si, Mn, Al, Zr, B, Ni, Ta, Nb, W, Ti, Mo, and Cr in a total of up to 5.0% by mass%. In addition, as impurity elements that are inevitably contained, for example, C, S, P, and O can be listed, and it is preferred that the upper limit of each of the elements is set to 0.1%, for example.
[0026] <Hot rolling process>
[0027] In the present embodiment, as an intermediate raw material of the Fe-Co alloy bar, a columnar Fe-Co alloy billet of about φ90 mm obtained from a Fe-Co alloy steel block having the above composition is hot rolled to obtain a hot-rolled bar. Since an oxide layer is formed on the intermediate raw material by hot rolling, a grinding process for removing the oxide layer mechanically or chemically can also be introduced. In addition, in the present invention, a hot-rolled bar having a length of more than 2 m is the object. The longer the hot-rolled bar is, the more the productivity in the heating straightening process is improved, but on the other hand, the longer the hot-rolled bar is, the easier it is to produce deviations in the magnetic properties in the length direction of the bar. According to the manufacturing method of the present invention, magnetic property deviations can be suppressed even in such long bars. Here, considering the processability in the subsequent process, the hot-rolled bar is preferably set to a diameter of 5 mm to 20 mm. For bars other than round bars, the area circle equivalent diameter of the cross section can also be set to 5 mm to 20 mm.
[0028] In the present embodiment, solution treatment is not performed during the transition from the hot rolling process to the heating straightening process described later. When solution treatment is performed, grain growth proceeds during solution treatment, and the grain boundaries that serve as recrystallization nucleation sites are reduced, thereby making it difficult to promote recrystallization during magnetic annealing. In the low compression ratio portion with a compression ratio of less than 2.5%, a mixed grain structure containing unrecrystallized grains is formed, thereby extremely deteriorating the magnetic properties. In addition, when solution treatment is performed, the bar sometimes bends due to thermal shrinkage. If the bend is corrected by the punching correction described later, it is difficult to obtain a stable compression ratio due to the work hardening caused by local strain. When solution treatment is not performed, recrystallization during magnetic annealing can be promoted by suppressing grain growth before the heating straightening process. Even in the region of compression ratios of 2.0% to 2.5%, the deviation of the grain size during magnetic annealing is small, and stable magnetic properties can be obtained. Here, the so-called solution treatment is a treatment in which the hot-rolled bar is heated at a temperature exceeding the regular-irregular transformation point (for example, 750°C to 1050°C) and then rapidly cooled, and the so-called compression ratio is a ratio obtained by dividing the difference in area before and after the heating straightening step by the area before the heating straightening step.
[0029] Before transferring to the heating and straightening process described later, a press correction for adjusting the shape of the bar material may be performed within the range of the compression rate of the present invention. By press correction, the subsequent heating and straightening process can be quickly performed. In addition, in the case where the solid solution treatment is not performed as in the present invention, it is preferred not to perform press correction with a high processing rate because there is a tendency that excessive bending does not occur. By not performing press correction, a stable compression rate can be obtained in the heating and straightening process.
[0030] <Heating and straightening process>
[0031] In this embodiment, for the hot-rolled material, a heating straightening process of imparting tensile stress while heating is performed. At this time, if the hot-rolled material is in the shape of a "bar", it is stretched along the length direction of the hot-rolled bar to impart the tensile stress. Through the process, a bar having very good magnetic properties and straightness can be obtained while imparting residual strain to the hot-rolled material. The heating temperature at this time is set to 500°C to 900°C. When it is lower than 500°C, the workability is reduced, and the bar may break when imparting tensile stress. On the other hand, when the heating temperature exceeds 900°C, the hot-rolled material cannot be given a preferred residual strain. The lower limit of the preferred heating temperature in the heating straightening process is 600°C, and more preferably 700°C. In addition, the upper limit of the preferred heating temperature is 850°C, more preferably 830°C, and more preferably 800°C. In addition, when the solution treatment process is omitted, the lower limit of the preferred heating temperature is 700°C, more preferably 730°C, and more preferably 740°C.
[0032] In the present embodiment, it is characterized in that the compression rate of the rod in the heating straightening process is adjusted to 2.0% to 8.0%. As a result, the rod can be given a strain that serves as a driving force for obtaining coarse grains, thereby obtaining a rod with less deviation in magnetic properties. The strain can be represented by the average value of the GOS value described later. The preferred lower limit of the compression rate is 2.2%, more preferably 2.5%, and the preferred upper limit of the compression rate is 7.5%. Regarding the compression rate of the present invention, the diameter before the heating straightening process and the diameter after the heating straightening process are measured using a micrometer to calculate, and the diameter is measured at multiple locations at equal intervals along the axial direction of the rod and derived. In the present embodiment, 28 locations are measured at equal intervals along the axial direction of the rod to obtain the compression rate distribution in a rod.
[0033] In the heating straightening process, heating methods such as electric heating and induction heating can be used. In terms of the effect of easily aligning the easy magnetization axis of the grains in the hot-rolled material in a certain direction, and the advantage of being able to quickly (for example, within 1 minute) and uniformly heat the material to the target temperature, it is preferred to apply electric heating. In addition, in order to more reliably obtain the required residual strain, the tensile load applied to the bar during the heating straightening process is preferably adjusted to 4kN to 90kN. In addition, it is preferably adjusted to an elongation of 3% to 10% relative to the total length before the heating straightening process. The Fe-Co alloy bar obtained by the manufacturing method of the present invention can make the compression rate of the bar 2.0% to 8.0% by appropriately adjusting these values while omitting the solid solution treatment.
[0034] Furthermore, in the heating straightening process using the electric heating applied in the present invention, since the clamping part is of equal voltage and the current does not flow, the temperature does not rise in the clamping part. In addition, the rod is mechanically constrained, so there is almost no elongation in the clamping part, which is the part that is cut and removed in the subsequent process. Therefore, in the present invention, the compression rate in the range from the end of the rod to 250 mm, which has a large influence on the clamping part in the heating straightening process, is not considered. Alternatively, in the method for manufacturing the Fe-Co alloy rod of the present invention, the compression rate of 2.0% to 8.0% can be achieved as long as it can be achieved within the range of at least 2 m of the continuous length of the rod.
[0035] In this embodiment, the bar material that has completed the heat straightening process can also be subjected to centerless grinding using a centerless grinder, for example. This can remove the black skin on the surface of the bar material, and further improve the roundness or tolerance accuracy of the shape. In the present invention, since the straightness of the bar material is improved by the heat straightening process, a long bar material with a length of more than 2 mm can also be subjected to centerless grinding without cutting.
[0036] Next, the Fe-Co alloy rod of the present invention that can be obtained by the manufacturing method of the present invention is described. The average value of the grain orientation spread (GOS) value of the Fe-Co alloy rod of the present invention is 0.3° to 1.5°. The preferred lower limit of the GOS average value is 0.5°, and the preferred upper limit of the GOS average value is 1.2°. The GOS value can be measured by the previously known "scanning electron microscope-electron backscatter diffraction (SEM-EBSD) method (electron beam backscatter diffraction method)". That is, by calculating the average value of the orientation difference between a point (pixel) constituting the grain and all other points in the grain, the operation is performed at all points in the grain, and the average value is calculated, so that the GOS value of the grain can be calculated. Here, since the GOS value is determined for each grain, two types of average values can be considered, namely, the number average and the area average, but the GOS average value referred to in the present invention represents the area average. The area average is a value calculated by weighting the GOS of the grains present in the measurement field of view by the area ratio of the field of view occupied by the grains and adding them. Moreover, the GOS average value can be used as an index to represent the strain given to the alloy by processing. Therefore, by making the GOS average value 0.3° to 1.5°, a strain suitable for obtaining coarse grains and serving as a driving force for recrystallization is introduced into the rod, and good magnetic properties can be obtained. In the case where the GOS average value is less than 0.3°, since the driving force for recrystallization is insufficient for the rod, the unrecrystallized grain area that has an adverse effect on the magnetic properties remains, and good magnetic properties cannot be obtained. In addition, in the case where the GOS average value exceeds 1.5°, the rod is given an excessive tensile tension, which is easy to be locally compressed, and it is believed that there is a disadvantage that stable magnetic properties cannot be obtained on the rod as a whole. In addition, the sections used to observe the GOS average value also include the section at right angles to the axis and the section in the axial direction, and the axial section can be observed. Furthermore, in both the case of observing the cross section in the direction perpendicular to the axis and the cross section in the axial direction of the rod, the GOS average value is preferably 0.3° to 1.5°.
[0037] The average crystal grain size number of the Fe-Co alloy bar of the present invention is preferably 8.0 or more and 12.0 or less. Thus, the grain boundary or triple point as the recrystallization nucleation site in magnetic annealing increases, and recrystallization easily occurs, thereby easily exerting stable magnetic properties. The lower limit of the more preferred average crystal grain size number is 8.5, and the upper limit of the more preferred average crystal grain size number is 11.5. And then the lower limit of the preferred average crystal grain size number is 9.0, and then the upper limit of the preferred average crystal grain size number is 11.0. In addition, the average crystal grain size number can be measured based on Japanese Industrial Standards (JIS) G 0551. And, it can be measured in the axial section of the bar. Alternatively, it can be measured in the cross section or axial section of the axis of the bar.
[0038] Furthermore, in the Fe-Co alloy rod of the present invention, it is preferred that the GOS average value or average grain size number is satisfied over the entire length of 2 m or more, but it can also be said that it only needs to be satisfied over a continuous length of at least 2 m.
[0039] Example
[0040] (Example 1)
[0041] An Fe-Co alloy steel block having a composition shown in Table 1 was divided into blocks and then hot-rolled to prepare hot-rolled bars having a diameter of 11.8 mm and a length of 2900 mm.
[0042] <Sample No. 1 to Sample No. 3>
[0043] The hot-rolled bars were not subjected to solution treatment, but were subjected to a heating straightening step of stretching the hot-rolled bars in their longitudinal direction under a tensile load of 27 kN while being heated to a temperature of about 750° C., thereby producing Fe—Co alloy bars of Samples No. 1 to No. 3 having a length of 3050 mm as examples of the present invention.
[0044] <Sample No. 4 to Sample No. 6>
[0045] After the hot rolled bar was subjected to a solution treatment of heating at 850°C and holding for 30 minutes and then rapidly cooled, a heating straightening step was performed to produce Fe-Co alloy bars of samples No. 4 to No. 6 having a length of 3050 mm as comparative examples. The conditions of the heating straightening step were the same as those of samples No. 1 to No. 3.
[0046] [Table 1]
[0047] (mass%)
[0048] C Si Mn Co V The remainder 0.006 0.03 0.13 49.20 1.98 Fe and inevitable impurities
[0049] The compression rate distribution of the prepared samples of the present invention and comparative examples was checked. The compression rate was calculated by measuring the diameter before and after the heating straightening process using a micrometer. The diameter was measured at 28 locations at equal intervals along the axial direction of the rod to obtain the distribution in one rod. The distribution of the compression rate in the rod is shown in FIG. Figure 1 and Figure 2 In the heating straightening process using electric heating, the clamping part has an equal voltage and the current does not flow, so the temperature does not rise in the clamping part. In addition, the rod is mechanically constrained, so there is almost no elongation in the clamping part, which is the part that is cut and removed in the subsequent process. Therefore, the compression rate in the range from the end of the rod to 250mm, which has a large influence on the clamping part in the heating straightening process, is not considered. Figure 1 and Figure 2 The maximum value, minimum value, average value, and standard deviation of the obtained compression ratio are shown in Table 2. Here, the maximum value, minimum value, average value, and standard deviation of the compression ratio of the examples of the present invention are derived from Sample No. 1 to Sample No. 3, and the maximum value, minimum value, average value, and standard deviation of the compression ratio of the comparative examples are derived from Sample No. 4 to Sample No. 6. From Table 2, it can be confirmed that although the average value of the compression ratio of the examples of the present invention is almost the same as that of the comparative examples, the difference between the maximum value and the minimum value of the compression ratio of the examples of the present invention is smaller, and the standard deviation is also smaller, so the deviation of the compression ratio of the examples of the present invention is suppressed compared with the comparative examples.
[0050] [Table 2]
[0051]
[0052] Then, the average grain size, GOS average value and DC magnetic properties of sample No. 3 of the present invention and sample No. 6 of the comparative example were confirmed. With regard to the average grain size, an optical microscope manufactured by Olympus was used to determine the comparison method of JIS G 0551. With regard to the determination of the GOS value, a field emission scanning electron microscope manufactured by Zeiss and an EBSD measurement and analysis system orientation imaging micrograph (OIM) manufactured by TSL were used. The measurement field was 600 μm × 600 μm, the step distance between adjacent pixels was 1.5 μm, and the grain size was determined based on the condition that the azimuth difference between adjacent pixels was 2° or more for observation, and the GOS average value was obtained based on the mapping of the obtained GOS value. With regard to the average grain size and the GOS average value, the central axis position in the longitudinal section (axial section passing through the central axis) was measured. Regarding the DC magnetic properties, after collecting samples from the obtained rods, magnetic annealing at 850°C for 3 hours was carried out, and the maximum magnetic permeability and coercive force were measured using a DC magnetization specific test device. These measurement results are shown in Table 3 together with the compression rate of the sample collection position. Regarding the sample collection positions of the present invention examples and comparative examples, the compression rates are set to four or three places near the maximum value, minimum value and center value. According to the results of Table 3, it can be confirmed that in the present invention examples, the average grain size number is larger than that of the comparative example (the grain size is smaller than that of the comparative example), and stable DC magnetic properties can be obtained relative to the fluctuations in the compression rate and the GOS average value (an indicator of strain), and the deviation is suppressed.
[0053] [Table 3]
[0054]
[0055] Next, the coercive force distribution of sample No. 2 of the present invention and sample No. 5 of the comparative example was measured. The coercive force was measured by collecting samples for magnetic properties from the rods, performing magnetic annealing at 850°C for 3 hours, and using a DC magnetization specific test device. The distribution of coercive force is shown together with the distribution of compression rate. Figure 3 and Figure 4 But in Figure 3 and Figure 4 The measurement position is in the range of 0mm~250mm and 2800mm~3050mm ( Figure 3 , Figure 4 The shadow part of the image is not studied because of the large influence of clamping. It can be confirmed that in the comparative example, the coercive force is extremely increased (degraded) in the part with a small compression rate, while in the example of the present invention, the degradation of the coercive force in the part with a small compression rate is suppressed, a stable coercive force is obtained, and the deviation is suppressed.
[0056] Next, for the examples of the present invention and the comparative examples, according to Table 3, Figure 3 and Figure 4 The relationship between the compression ratio and the coercivity derived from the results is shown in Figure 5 In the range of compression rate of 2.5% or more, the comparative example shows excellent coercivity. Although the inventive example is inferior to the comparative example, it also shows excellent coercivity. In the range of compression rate of 2.5% or less, the coercivity of the comparative example deteriorates sharply and shows very unstable coercivity. It can be confirmed that in the inventive example, a stable coercivity is obtained even in the range of compression rate of 2.0% to 2.5%, and the deviation is suppressed.
Claims
1. A method for manufacturing a Fe-Co alloy bar, comprising: A hot rolling process is to hot-roll the Fe-Co alloy billet to obtain a hot-rolled bar with a length of more than 2 m; as well as In the heating straightening step, the hot-rolled bar is heated to 500° C. to 900° C., while applying tensile stress so that the bar has a compression rate of 2.0% to 8.0%. No solution treatment is performed between the hot rolling step and the heating and straightening step.
2. An Fe-Co alloy rod having an average value of grain orientation extension of 0.3° to 1.5°, an average grain size number of 8.0 to 12.0 measured in an axial section of the rod, and a length of 2 m or more.
Citation Information
Patent Citations
Production of wire rod of fe-co-v alloy
JP1995166239A
METHOD FOR MANUFACTURING Fe-Co-BASED ALLOY ROD, AND Fe-Co-BASED ALLOY ROD
WO2021182518A1